Unprovenanced Antiquities: Learning the Hard Way - Cargill, Bob (Biblical archaeology review, 2020)
The article offers information on warning provided to the Museum of the Bible about the problems surrounding the purchase and exhibition of unprovenanced, black-market antiquities. Topics include examines that the museum announced that an additional artifacts, papyri fragments and clay objects found to have been stolen from Iraq and Egypt and sold to Museum Chairman of the Board and chief benefactor.